Love your life : O's handbook for your best today-- and tomorrow - Winfrey, Oprah (Oxmoor House ; Time Home Entertainment, 2010)
"How can I stretch myself to my greatest potential?" With this brand-new collection of wit and wisdom from O, the Oprah magazine, discover advice you can really trust about health and fitness, family and friends, your finances and your future. Learn the secrets to making and sustaining a love connection, getting through tough times in one piece, and finding lasting happiness. Set aside time for self-reflection, and give a little something back to our communities and our world--Back cover.